The Effect of Stock, Government Policy, and Monopoly on Asymmetric Price Transmission in Thailand - Patanakorn, Prasarn; Pornchaiwisetgul, Pongsarn (International Journal of Energy Economics and Policy, 2015)
The article studies of asymmetric price transmission of gasoline price and diesel price and their causes in Thailand. The study employs the monthly data of West Texas Instrument crude oil price, unleaded gasoline price and high speed diesel price, the oil fund, the stock of unleaded gasoline and high speed diesel inventories. The results show that asymmetric price transmission exists for unleaded gasoline but not for high speed diesel. The oil fund does not influence on the price asymmetry. Whether the oil fund is levied, the price asymmetry always presents for unleaded gasoline but not for high speed diesel. Moreover, the marketing margins or firms' profits do not cause the asymmetric price for both. However, the oil fund and the marketing margins could make unleaded gasoline prices adjust more quickly but high speed diesel more slowly. The government is successful to use the oil fund directly to regulate the market gasoline and diesel price. The firms' monopoly power could also indirectly maintain those prices stable and make unleaded gasoline price adjust more slowly and high speed diesel more quickly. Finally, the stocks of unleaded gasoline and high speed diesel do not have the effects on the price asymmetry. The asymmetry is influenced mainly by the oil fund and the marketing margins. Firms do not need to adjust their price and their quantity. Keywords: asymmetric price transmission, oil fund, marketing margins, and stock of inventories. JEL Classifications: C32; Q41; Q48